2002
DOI: 10.4141/s00-093
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil texture on snowmelt infiltration into frozen soils

Abstract: Zhao, L., Gray, D. M. and Toth, B. 2002. Influence of soil texture on snowmelt infiltration into frozen soils. Can. J. Soil Sci. 82: 75-83. This paper describes the influence of soil texture on snowmelt infiltration into frozen soils. Field data collected on frozen, unsaturated agricultural soils of the Canadian Prairies during snow ablation demonstrate: (a) poor association between the amount of infiltration of meltwater released by the seasonal snowcover and soil texture, and (b) small differences in cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Kane and Stein (1983a) found that soil moisture formed an ice lens close to the soil surface during winter that limited water infiltration. In addition (Zhao et al, 2002) suggested that with most soil textures, water infiltration during snow-melt was limited to the top 10 cm of soil even if ice lenses are not present. The limitation for the upland sites was closer to the 20 cm depth based on soil moisture content estimates.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kane and Stein (1983a) found that soil moisture formed an ice lens close to the soil surface during winter that limited water infiltration. In addition (Zhao et al, 2002) suggested that with most soil textures, water infiltration during snow-melt was limited to the top 10 cm of soil even if ice lenses are not present. The limitation for the upland sites was closer to the 20 cm depth based on soil moisture content estimates.…”
Section: Discussionmentioning
confidence: 97%
“…This was measured to be in the range of 30-70 mm of the snowpack water at Palmer, Alaska (Branton et al, 1971) and simulated at 21% of the precipitation input in Arctic Alaska (Liston and Sturm, 2002). During the snowmelt period the infiltration of water into the surface soil will be controlled by the quantity of ice in the profile (Kane and Stein, 1983a,c;Gray et al, 2001;Zhao et al, 2002). Kane and Stein (1983a) found that soil moisture formed an ice lens close to the soil surface during winter that limited water infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…However, once sites north of 51°N reached 0°C they warmed faster than the sites south of 51°N, meaning planting dates were closer together at the sites north of 51°N (Table 3). This is due to the later disappearance of snow cover, increased available solar radiation when sites north of 51°N reached 0°C, and greater heat holding capacity of heavier texture clay loam soils relative to the sites south of 51°N (Zhao et al, 2002). The trial sites north of 51°N include soils classified as gray wooded Luvisols, orthic black chernozems, and orthic dark brown chernozems.…”
Section: Growing Season Variability and Environmental Conditionsmentioning
confidence: 99%
“…For example, in the study by Zhao et al (2002), infiltration into a lighter-textured sandy loam after 24 h was on average 23% higher than into the clay, silty clay loam and silt loam soils. Hardie et al (2011) also pointed out the importance of macropores on DP.…”
Section: Influences Of Soil Properties On Dpmentioning
confidence: 90%